Староверие Литвы в 1944-1953 гг.: «новый курс» советских властей, деятельность ВСС, изменение численности поморских общин - Potashenko, Grigorijus (Acta Neophilologica, 2022)
This article examines the relationship between Soviet authorities and the Pomorian Old Believer Church of Lithuania during 1944-1953, in particular, the position and organizational activities of the Supreme Old Believer Council in Vilnius, the plan to establish a central body of the bespopovtcy in the USSR. It also researches the question as to how the religious policy of the Soviet authorities at that time and the position of the leadership of the Church influenced the changes in the network of Pomorian communities in Lithuania. It is important to show the different types of communication between the authorities and the leadership of the Church within the framework of “the new course” of religious policy and in subsequent years. So far, these issues have been insufficiently or fragmentarily studied in historiography due to the limited use of archival material. Therefore, this article employs generalized data from materials relevant to our topic found in three archives of Lithuania – the State Central Archives of Lithuania, the Lithuanian Special Archives and the archive of the Supreme Old Believer Council of Lithuania in Vilnius.